From Reflection to Action: Empowering Students’ Multicultural Self-Efficacy through Youth Participatory Action Research (YPAR) Group Counseling - Ratu, Bau; Puswiartika, Dhevy; Nurwahyuni, Nurwahyuni; Arifyadi, Azam; Fitriani, Dian; Hasan, Hasan; Lakadjo, Mohamad Awal (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study investigates the effectiveness of multicultural group counseling integrated with the Youth Participatory Action Research (YPAR) approach in enhancing multicultural self-efficacy among Indonesian high school students. Using a mixed-methods method, nine students were selected through purposive sampling based on their willingness to participate, representation of cultural diversity, and absence of serious psychological concerns. They completed an eight-session YPAR-based group counseling intervention. Quantitative data were collected using the Multicultural Self-Efficacy Scale–High School Version (MSES–HS) and analyzed using descriptive statistics, the Wilcoxon signed-rank test, and effect size calculations. The results revealed a substantial increase in multicultural self-efficacy (ΔM = 88.78), representing approximately 49.8% of the total scale range, with all five dimensions—cultural knowledge, cultural values, cultural awareness, communication, and flexibility—showing significant improvement (p < .01; r = .89). Qualitative data derived from reflection journals, focus group discussions, and facilitator observations indicated enhanced intercultural empathy, increased communication confidence, and a shift from passive tolerance to proactive engagement. These findings align with Bandura’s self-efficacy and social learning theories and Corey’s group counseling framework, which emphasize experiential learning, peer modeling, and reflective dialogue. The integration of YPAR into multicultural counseling not only demonstrated statistical effectiveness but also fostered agency, cultural identity development, and a more participatory school climate. This study offers a culturally responsive and scalable intervention model for inclusive education, particularly in multicultural contexts such as Indonesia.